Evaluation method and module design for cost-effective compliance with irradiance guidelines to maintain soil quality in solar parks - Cesar Ilkay; Van Aken Bas B. (EPJ Photovoltaics)
Ground mounted solar parks lead to changes in the micro-climate under and between the PV tables. In particular, the vegetation on the soil is, in various degrees, shaded from direct sunlight and indirect, diffuse light. Also, the changes in precipitation distribution, air temperature and wind speed will affect the conditions. This leads to varying conditions for the vegetation affecting photosynthesis, which on the longer term influences the soil quality. To ensure sufficient light for photosynthesis, initial thresholds for irradiance have been drafted by TNO and Wageningen University and Research for the climate conditions in the Netherlands. Based on these rules, we present for the first time a method to evaluate the trade-off between soil irradiance and energy yield, related to table configuration and module choice, for utility-scale solar parks. Irradiance on the ground has either passed around the PV tables, passed through the gaps between panels or is transmitted between the solar cells in the panels. This leads to an optimisation of the module transparency and the size and relative position of the PV tables, when minimising the costs and at the same time complying with these irradiance criteria. To illustrate this optimisation, we have simulated the annual energy yield and ground irradiance and calculated the effect on the levelised cost of electricity. We present two solar park designs, that have the same ground irradiance distribution. One design is installed with partially transparent, bifacial modules, the other with gaps between the opaque, bifacial modules. Although the transparent bifacial modules have a somewhat lower module power, this system produces more kWh per hectare and has a lower levelised cost of electricity. The present paper shows that the partial transparency of bifacial modules is a key feature to maintain the soil ecology, and profitability, thus contributing to societal acceptance.